Princess Diana’s Pregnancy: New Forensic and Mathematical Evidence - Salerian, Alen J (European Journal of Applied Sciences, 2025)
On August 31st 1997, Diana, Princess of Wales died in a car crash in Paris, France on August 31st 1997. Dodi Fayed, Diana’s partner, and the driver, Henri Paul, were also killed. Thee deaths of Princess Diana, Dodi Fayed and Henry Paul resulted from Paul ‘s reckless driving and the pursuing paparazzi was the conclusion of a British inquest, Operation Paget,in 2008. Since 1997 there have been allegations that Princess Diana became a victim of intelligent homicide because of her pregnancy associated social turmoil. Objective: To answer,” Was Princess Diana pregnant at the time of her death. Method: We reviewed” Coroner’s Inquests into the Deaths of Diana, Princess of Wales and Mr Dodi Al Fayed computer Aided Modelling Bureau, Metropolitan Police Service November 2007” and applied the probability theory to project odds of certainty that Princess Diana was pregnant and her pregnancy contributed to her death by Intelligent homicide and cover up. Results: 11 observations consistent with” Princess Diana was pregnant” and “inconsistent with that she was not,” suggest that princess Diana was pregnant. The odds of this conclusion being correct is %99.9. 10 observations consistent with “psychosocial factors contributed to her death” and “inconsistent with they did not” suggest that Princess Diana’s pregnancy contributed to her death by intelligent homicide. Discussion: Evidence suggests that Princess Diana , was pregnant and her pregnancy contributed to her death by intelligent homicide. Conclusion: Princess Diana’s pregnancy contributed to her death by intelligent homicide.